Biofuels subsidies and the green paradox - R. Quentin Grafton; Tom Kompas; Ngo Van Long (Center for Economic Studies and ifo Institute (CESifo), 2010)
This paper develops sufficient conditions under which the Weak Green Paradox may (and may not) hold in terms of subsidies for biofuel production such that the supply-side responses by fossil fuel producers may more than offset the substitution to biofuels. Analytical results are derived and numerical simulations show that, under a wide range of parameter values, biofuel subsidies will increase the rate of extraction of fossil fuels in the short and medium term, and possibly bring climate-change damages closer to the present.
Keywords: Q54; Q42; Q30; 330; biofuels subsidies; the Green Paradox; Biokraftstoff; Subvention; Wirkungsanalyse; Kraftstoff; Fossiler Energieträger; Angebot; Reaktionsfunktion; Klimaveränderung; Theorie